The INDIAN STATUS IN THE FDI FLOWS IN THE WORLD - Altaf hussan dar,Dr. Vipin Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Countries around the world, both developed and developing, are working together to encourage bigger FDI flows into their economy. In an attempt to lure bigger FDIs to India, the Indian government leaves no stone untouched. However, although India provides a vast market potential, has a pool of experienced, qualified and bright employees, low labor costs and a liberal democratic political structure, FDI inflows into India have remained modest compared to other rising economies. In this context, the status of FDI flows into India and identifies the concerns and problems which have made India more appealing than other countries. In this study we examine the status of Indians in the FDI world flows, the FDI picture in India's indigenous economy, FDI growth in developed countries, and the flow of FDI in Asia. Asia is by both nominal and purchasing power parity GDP the world's fastest-growing economic area and the largest continental economy